Dentists' knowledge, beliefs and behaviours on preventing Covid-19 transmission in Turkey: A Health Belief Model study (Annals of Medical Research, 2022)
Aim: This study aimed to evaluate the knowledge, beliefs, and behaviors of dentists in preventing Covid-19 transmission using the Health Belief Model.Materials and Methods: This descriptive study was conducted on 432 dentists who returned to the study tool in an electronic environment. The data were collected by a questionnaire and Health Belief Model Form for protection from Covid-19 (HBMF-COVID-19).Results: Most participants had knowledge about Covid-19, including its symptoms, transmission path, and incubation period. More than 90% of the participants knew the precautions to be taken in a dental clinic. Although the participants were largely aware of all preventive behaviors, the rate of performing these behaviors were lower. Wearing a protective overall (31%), wearing an FFP (filtering facepiece) mask (61.8%), and patient isolation (70.4%) were the measures least taken. The total mean score of HBMF-Covid-19 was 3.71 ± 0.33. Barrier perception had the lowest sub-dimension median score (2.50).Conclusion: Although dentists know the measures, they have not taken enough precautions to protect themselves and patients from Covid-19. Having low barrier perception scores point to, there are situations that prevent dentists from performing preventive behaviors at workplaces. It is recommended to use the Health Belief Model to determine the factors that prevent and facilitate dentists' preventive behaviors. Considering the results, training and awareness activities can be planned by public health nurses.
Keywords: Covid-19; Dentist; Health Belief Model; Health Behavior; Health Perception